Asymmetric Oil Price Pass-Through to Disaggregate Consumer Prices in Emerging Market: Evidence from Indonesia - Widarjono, Agus; Hakim, Abdul (International Journal of Energy Economics and Policy, 2019)
This study investigates the inflationary asymmetric effects of oil prices at disaggregate consumer prices for Indonesia using Non-linear Autoregressive Distributed Lag model (NARDL). The bound tests for cointegration affirm the existence of a long-run relationship between oil prices and the aggregate consumer price (CPI) and its all sub-components. With the exception of the education price index, our results suggest the asymmetric effect of oil price on all sub-components of CPI. The degree of oil price pass-through is an incomplete degree but varied among sub-components of CPI and is attributed to energy-related goods and services. The highest degree of oil price pass-through is foodstuffs price index, followed by the transportation price index. We also find the positive degree of oil price pass-through to disaggregate consumer price is higher than the negative degree of oil price oil pass-through to disaggregate consumer price. Keywords: Oil price, Disaggregate consumer prices, NARDL, Indonesia, JEL Classifications: C22; E31 DOI: https://doi.org/10.32479/ijeep.8287